Pengaruh Pertumbuhan Perusahaan, Profitabilitas, Solvabilitas dan Opini Audit Going Concern Tahun Sebelumnya Terhadap Opini Audit Going Concern Pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia - Julfan Saputra; Eka Nurmala Sari; Widia Astuty (Jurnal Riset Akuntansi dan Bisnis, 2021)
This study aims to determine how much influence the company's growth, profitability, solvency and previous year's going concern audit opinion has on going concern audit opinion on mining companies listed on the Indonesia Stock Exchange. The population used in this study are all mining companies listed on the Indonesia Stock Exchange in 2014-2018. The analysis technique in this study is logistic regression and descriptive statistics with the help of the SPSS program. The results showed that: 1) company growth has no effect on going audit opinion concern..2) profitability has an effect on going concern audit opinion. 3) solvency has no effect on going concern audit opinion. 4) the previous year's going concern audit opinion affects the going concern audit opinion. 5) there is asimultaneous n company growth, profitability, solvency and previous year's going influence on audit opinion on going concern